Financial Engineering for Cost Efficiency, Risk Control, and MSME Competitiveness in Sidoarjo Cracker Industry - Nursitti Khumairoh; Mochammad Hatta (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
Purpose: This study develops a practical financial engineering model to improve cost efficiency, financial risk control, and competitiveness among micro, small, and medium enterprises (MSMEs) in the cracker industry of Sidoarjo Regency, East Java, Indonesia. Design/methodology/approach: The study applies a descriptive qualitative design supported by structured secondary-data extraction. Data were collected from government publications, MSME directories, previous studies, journal articles, institutional reports, and relevant online business sources. A total of 200 data items were organised into four analytical domains: cost structure and financial risks, financial engineering instruments for cost efficiency, financial risk control and competitiveness, and financial engineering model development. Findings: The findings show that cracker MSMEs operate in a cost-sensitive environment shaped by raw material price volatility, energy costs, manual labour intensity, limited working capital, delayed payments, and informal pricing. Practical financial engineering instruments, including costing sheets, unit cost calculation, break-even point analysis, contribution margin analysis, working capital control, receivable monitoring, and a simple risk register, can improve pricing accuracy, liquidity discipline, and business resilience. Research limitations/implications: The research object was local cracker business units and production clusters, particularly those associated with Kedungrejo-Jabon, Krembung, Tulangan, Porong, and other village-based MSME areas. Practical implications: The proposed model can guide MSME owners, local government, cooperatives, and business mentors in designing cost-calculation training, digital bookkeeping assistance, risk-based pricing, and working-capital control programmes. Originality/value: This article contributes a contextual financial engineering framework for food-based MSME clusters by integrating cost efficiency, financial risk control, and competitiveness improvement in one practical model. Paper type: Research Paper